Macroeconomic Development and Dramatic Increase in Stroke Burden in Rural China: A 25-Year Population-Based Study - Zhao, Peng; Liu, Jie; Hao, Yuhan; Lin, Qiuxing; Gao, Ying; Tu, Jun; Wang, Jinghua; Wang, Yaogang; Ning, Xianjia (Frontiers in Neurology, 2020)
Low socioeconomic status is associated with a high stroke risk. However, few studies have quantitatively assessed the relationship between stroke burden and national economic development indicators. We explored the quantitative association between macroeconomic development and stroke burden in rural China. In this population-based, prospective study (1992–2016), we collected data on annual registrations of stroke events and deaths in Tianjin, China. Economic development over the period was represented by gross domestic product annually adjusted for purchasing power parity (PPP-aGDP) and per capita net income (PCNI) of rural residents in China. We assessed the association of first-ever stroke incidence with PPP-aGDP and PCNI. During the 25-year study period, there were 1185 stroke events and 362,296 person-years of surveillance. First-ever stroke incidence increased by an average of 10.7% per 1000 USD increase in overall PPP-aGDP and by 12.0% per 1000 Yuan increase in PCNI; respectively, the mean increases were 9.6% and 10.8% in men and 13.0% and 14.4% in women (all, P < 0.001). These same changes in PPP-aGDP and PCNI also resulted in increases in the incidence of ischemic stroke (12.6% and 14.3%, respectively; P < 0.05), and intracerebral hemorrhage (both, 6.2%; P < 0.05). Similarly, in men, the age of onset of intracerebral hemorrhage decreased by 0.96 years (P = 0.002) for each 1000 USD increase in PPP-aGDP and by 1.08 years (P = 0.003) for each 1000 Yuan increase in PCNI. Macroeconomic development was positively associated with stroke incidence in rural China. Thus, enhancing health-care investments is crucial for containing the stroke burden during this remarkable economic development in China. Our findings could guide other developing countries with information regarding the timely control of stroke risk factors and reductions in stroke burden during the initial stages of economic development.